Production of polylactic acid nanoparticles encapsulating astaxanthin - Ibrahim Ali, Noorbatcha; Ahmad Zawawi, Ahmad Fandi; Ali, Fathilah; Jaswir, Irwandi (2016)
Astaxanthin is one of the carotenoid that has high antioxidant characteristics among other carotenoids. Hence it can play an active role in the prevention of cancer and cardiovascular diseases. However, its use as a high value pharmaceutical product is limited by its low water solubility and bioavailability. Nanoencapsulation of active materials in a biodegradable polymer matrix can be used to alleviate this problem. In addition to increasing the stability of the active compounds inside the matrix, nanoencapsulation can also be used to manipulate the controlled and sustained release of active materials into the target area. Poly-lactic acid (PLA) is a good drug carrier based on its biodegradability and biocompatibility. PLA have been reported as an encapsulated material and delivery vehicle for several active compounds. In this study, PLA along with poly-vinyl alcohol (PVA) was used to encapsulate astaxanthin using single emulsion method. The effect of PLA and PVA concentration on drug loading and drug entrapment was analyzed, and the optimum conditions for high drug loading were found to be 8.71 mg of PLA and 8.26 % of PVA solution. The in-vitro drug release of astaxanthin from the nanoparticles shows an initial burst profile followed by a slow release until 24 hours.